Wet ball milling of niobium by using ethanol, determination of the crystallite size and microstructures - Azunna Agwo Eze (Nature Portfolio, 2021)
Abstract This study investigates the effect of using ethanol as the process control agent during the wet ball milling of niobium (Nb). Dried nanocrystal Nb powders, of high purity, with particle sizes, ranging from 8.5 to 14.3 nm, were synthesized by ball milling. Commercial Nb powder of particle sizes of − 44 µm was employed by using the planetary ball mill equipped with stainless still vials with still balls in ethanol. A ball-to-powder mass ratio of 10:1 was used at a rotation speed of 400 rpm, an interval of 15 min with an interval break of 5 s, and a milling time of 10 h. The powder was dried in vacutec at a temperature of 100 °C, using a speed of 15 rpm in the vacuum of 250 mbar at a time of approximately 653 min. The crystal phase of the dried powders was analyzed using X-ray diffraction (XRD) with CuKɑ radiation, and by modification of the Scherrer equation, a single crystallite size of 11.85 nm was obtained. The morphology of the particles was observed using scanning electron microscopy (SEM) with energy-dispersive X-ray spectroscopy (EDS). The XRD results show that the pure crystal sizes in nanometre (nm), which decreases as the 2θ and the full width at half maximum (FWHM) increases.